Pre-induction cervical assessment using transvaginal ultrasound versus bishops cervical scoring as predictors of successful induction of labour in term pregnancies: a hospital-based comparative clinical trial - Abang Abdullah, Zainab Hananah; Chew, Kah Teik; V. Velayudham, V. Ramesh; Yahaya, Zainab; Mohd Jamil, Amilia Afzan; Abu, Muhammad Azrai; Abdul Ghani, Nur Azurah; Mohamed Ismail, Nor Azlin (Public Library of Science, 2022)
Objective To evaluate the association between transvaginal ultrasound scan of cervix and Bishop’s score in predicting successful induction of labour, cut-off points and patients’ tolerability and acceptance for both procedures.